2018
DOI: 10.1155/2018/5287573
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Parathyroid Hormone and Vitamin D Serum Concentrations in Patients with Cardiovascular Diseases

Abstract: 25-hydroxyvitamin D (25(OH)D) plays a crucial role in human homeostasis. Its deficiency (vitamin D deficiency—VDD), being common in European population, combined with elevated concentration of parathyroid hormone (PTH), represents a vicious cycle of mechanisms leading to heart failure (HF). Despite several papers published in that field, the effect of VDD and PTH concentration on cardiovascular system remains unequivocal; thus, the aim of the study was to compare these data among HF and non-HF patients being p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…[8] It is demonstrated that elevated serum PTH level is an independent factor in myocardial injury and all-cause mortality in post-MI patients. [3334] In the current study, atorvastatin did not reverse the increasing of PTH level after acute MI in Vitamin D-deficient/insufficient patients but caused a nonsignificant drop in PTH in Vitamin D-sufficient patients. It has been proposed that the ability of atorvastatin 80 mg daily might not be enough to reduce serum PTH level; however, it seems that the modifying effect of atorvastatin on serum PTH level might be depending on Vitamin D status.…”
Section: Discussioncontrasting
confidence: 43%
“…[8] It is demonstrated that elevated serum PTH level is an independent factor in myocardial injury and all-cause mortality in post-MI patients. [3334] In the current study, atorvastatin did not reverse the increasing of PTH level after acute MI in Vitamin D-deficient/insufficient patients but caused a nonsignificant drop in PTH in Vitamin D-sufficient patients. It has been proposed that the ability of atorvastatin 80 mg daily might not be enough to reduce serum PTH level; however, it seems that the modifying effect of atorvastatin on serum PTH level might be depending on Vitamin D status.…”
Section: Discussioncontrasting
confidence: 43%
“…[17] PTH is a critical regulator of bone and mineral metabolic process, and its biosynthesis is influenced by changes in blood calcium levels, which trigger responses in several pathways. [18] PTH levels in relation to 25(OH)D levels are often used to determine Vitamin D insufficiency levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was highly significant, above (p < 0.001) than in the studied population. and ethnicity-dependent vitamin D doses ranging between 400 and 2000 IU/day [18,19].…”
Section: Discussionmentioning
confidence: 99%